Sunitinib in the treatment of renal cell carcinoma: an update on recent evidence - Mimma Rizzo; Camillo Porta (Therapeutic Advances in Urology, 2017)
Sunitinib is a multitarget tyrosine kinase inhibitor endowed mainly by antiangiogenic effects, although an indirect inhibitory effect on tumor growth and, more recently, a complex activity on antitumor immune response has been described. From approval by the US Food and Drug Administration (FDA) in January 2006, sunitinib represents a key molecule in the treatment of metastatic renal cell carcinoma (mRCC) due to the peculiar molecular pathogenesis of this neoplasm. Over the past 10 years, clinical trials and real-world experiences helped clinicians to understand how, when and for how long to use sunitinib. Although a huge amount of data evidenced the relationship existing between sunitinib dose intensity and improved clinical outcome, the management of sunitinib-induced adverse events is often complex; thus, alternative schedules have been proposed over time which allow increased tolerability, without decreased daily sunitinib exposure, leading to improved clinical outcomes. To date, combinations of sunitinib with other approved targeted agents did not demonstrate any significant benefit over its single-agent use, mainly due to tolerability issues. Sunitinib has also been tested in the adjuvant setting, within the ASSURE and S-TRAC trials, with opposite results; indeed, equivocal risk-stratification criteria, as well as immature overall survival (OS) data prevent any definitive conclusion on this important issue. Despite being on the market for a long time, sunitinib still plays a role as the ‘comparator arm’ of a number of trials in the field of mRCC. Combinations with immune checkpoint inhibitors and vaccines look promising; once again, sunitinib can help us to optimize mRCC management.